2016
DOI: 10.1590/2237-6089-2015-0067
|View full text |Cite
|
Sign up to set email alerts
|

Special features of high-risk pregnancies as factors in development of mental distress: a review

Abstract: Introduction: Approximately 22% of all pregnant women are classified as having high-risk pregnancies, which may involve feelings of vulnerability because of having a high-risk pregnancy, resulting in greater exposure to stressful feelings. Objective: To review aspects of high-risk pregnancy that can have a negative impact on the these women's mental health status. Method: Original articles were identified by conducting searches of the PubMed/MEDLINE, LILACS and SciELO databases, followed by a manual search of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Additionally, in a study in which 42 pregnant women were assessed using the WHOQOL-Bref, it was observed that the subjects had a good general quality of life. It also demonstrated that the WHOQOL-Bref is pertinent as a monitoring instrument, thus permitting the expansion of prenatal care ( 16 ). In this study, we also used the WHOQOL-Bref since there is no specific questionnaire for assessing the quality of life of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in a study in which 42 pregnant women were assessed using the WHOQOL-Bref, it was observed that the subjects had a good general quality of life. It also demonstrated that the WHOQOL-Bref is pertinent as a monitoring instrument, thus permitting the expansion of prenatal care ( 16 ). In this study, we also used the WHOQOL-Bref since there is no specific questionnaire for assessing the quality of life of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…After being diagnosed with risky pregnancy and PE and during hospitalization, these women have a better perception of their disease and they start to question themselves about what led to their current condition. This may generate a feeling of guilt and anxiety, with a consequent change in their quality of life ( 13 - 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the 1960s, literature started referring to the concept of high-risk pregnancy [8]. Roderigues et al [9] reveal that healthcare providers consider the label of high-risk pregnancy to be an indication that a woman and/or her unborn infant are at risk of both physical and psychological harm.…”
Section: Introductionmentioning
confidence: 99%
“…HRP is associated with different physical complications which in turn can cause mood changes and mental and social problems. Studies showed that women with HRP experience negative feelings such as restlessness, fear, loss of control, disability, anger, and anxiety (3)(4)(5). A qualitative study also showed that besides medical problems, women with HRP experience behavioral, affective, and emotional problems as well as problems in personal and familial role performance.…”
Section: Introductionmentioning
confidence: 99%